Acantocephals and nematodes of fish of waters of the medium flow of the Zarafshan river - Akramova Firuza Jalaliddinovna; Soatov Bakhrom Bakhtiyorovich; Safarova Feruza Ergashevna (International Journal on Orange Technologies, 2020)
The basin of the Zarafshan River is a natural-geographical complex on a transboundary territory, in which there are reservoirs of different ecological conditions. At present, a large number of large reservoirs for complex use with an area of hundreds of thousands of hectares have been created in the Zarafshan river basin. Reservoirs are a new type of water bodies, differing in specific and ecological conditions [2].